PENGARUH KARAKTERISTIK PERUSAHAAN DAN KOMPENSASI MANAJEMEN EKSEKUTIF TERHADAP KINERJA KEUANGAN - Yeni Maulidia; Erika Astriani Aprilia (Program Studi Ekonomi Syariah, 2023)
This study aims to examine the effect of firm characteristics, including leverage and firm size, as well as executive management concealment on financial performance. This study uses financial performance as the dependent variable and company characteristics by proxy for leverage and firm size and executive management as independent variables. This type of research is associative research. This study uses secondary data in the form of annual financial reports from the Indonesia Stock Exchange (IDX). The population in this study are Primary Consumer Sub-Sector Companies listed on the Indonesia Stock Exchange for 2017-2021. The sampling technique in this study used a purposive sampling method, obtained 32 companies as research samples. The data analysis technique in this study used multiple linear regression analysis and the data analysis tool in this study used the Eviews version 12 software program. The results showed that (1) the characteristics of companies with leverage proxies and firm size simultaneously affect financial performance, (2) The characteristics of companies with a proxy for leverage have a significant positive effect on financial performance, (3) The characteristics of companies with a proxy for firm size have no significant effect on financial performance, (4) Executive management compensation has no significant effect on financial performance